2001
DOI: 10.1136/vr.148.20.619
|View full text |Cite
|
Sign up to set email alerts
|

Jugular venous emboli of brain tissue induced in sheep by the use of captive bolt guns

Abstract: Emboli of central nervous tissue were detected in the jugular venous blood of two of 15 sheep stunned with a conventional cartridge-operated captive bolt gun and in two of 15 sheep stunned with a pneumatically activated gun. No emboli were detected in arterial blood from these sheep or in venous blood from sheep stunned electrically. Emboli from an animal with BSE could transmit the disease to people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…Nevertheless, potential problems associated with this type of gun, such as the frequent recovery before sticking, need to be resolved (EFSA, 2004). The use of electrical stunning seems to be another safer option (Anil et al, 2001). This method is used in different countries, namely New Zealand, Australia and the United Kingdom (Wotton, Gregory, Whittington, & Parkman, 2000); however, its high cost and some doubts about animal welfare associated with the ineffective use of this method need to be addressed (Heim, Löpfe, Mumford, & Speedy, 2007).…”
Section: Cattle Stunningmentioning
confidence: 99%
“…Nevertheless, potential problems associated with this type of gun, such as the frequent recovery before sticking, need to be resolved (EFSA, 2004). The use of electrical stunning seems to be another safer option (Anil et al, 2001). This method is used in different countries, namely New Zealand, Australia and the United Kingdom (Wotton, Gregory, Whittington, & Parkman, 2000); however, its high cost and some doubts about animal welfare associated with the ineffective use of this method need to be addressed (Heim, Löpfe, Mumford, & Speedy, 2007).…”
Section: Cattle Stunningmentioning
confidence: 99%
“…Venous blood from the head of CB stunned cattle and sheep has been shown to contain small brain emboli (≥5 μ m), as well as a CNS specific protein, syntaxin 1B (Anil et al. 1999; Anil et al. 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that no CNS tissue was detected in either aortic or venous blood samples collected from cattle or sheep after using these two devices. [48][49][50] However, other studies have detected brain tissue in venous blood samples from stunned cattle, [55] and on the surface of beef carcasses [43] after non-penetrating stunning. There also is an increased risk to operators as some animals may be inadequately stunned with non-penetrating stunning and recover their consciousness during slaughtering.…”
Section: Non-penetrative Stunningmentioning
confidence: 97%
“…[54] However, the use of pneumatic-powered stunners and cartridge-fired stunners produced visible CNS clots in 12 and 1% of the cattle heart samples, respectively. [51] In addition, after using this type of stunner, CNS tissue was detected in the jugular venous blood from sheep, [49,50] in venous blood from cattle, [55] in bovine pulmonary arterial system, [56] and on the surface of beef carcasses. [43] In a study designed to trace the spread of CNS tissue in the cattle body after stunning with a cartridge-fired stunner, a marker microorganism, Pseudomonas fluorescens, was inoculated into the bovine brain via the stunning procedure.…”
Section: Penetrative Stunning Without Air Injectionmentioning
confidence: 99%
See 1 more Smart Citation